Forest succession improves the complexity of soil microbial interaction and ecological stochasticity of community assembly: Evidence from Phoebe bournei-dominated forests in subtropical regions - He, Gongxiu; Peng, Tieshuang; Guo, Yi; Wen, Shizhi; Ji, Li; Luo, Zhong (Frontiers in Microbiology, 2022)
Forest succession is a central ecological topic, due to the importance of the associated dynamic processes for terrestrial ecosystems. However, very little is currently known about the community assembly and interaction of soil microbial communities along forest successional trajectories, particularly regarding the microbial community dynamics in contrasting seasons. To bridge these knowledge gaps, we studied soil bacterial and fungal community compositions, assemblages, and co-occurrence networks in a well-established successional gradient of Phoebe bournei-dominated forest, spanning about 65 years of forest development in a subtropical region. Illumina MiSeq sequencing of 16S and ITS genes was employed for the assessment of soil bacterial and fungal community composition and diversity, respectively. The relative abundance and α–diversity of soil bacteria and fungi showed a differential trend over forest succession. The dominant fungal phyla (Basidiomycota and Ascomycota) changed more frequently than the dominant bacterial phyla (Proteobacteria, Acidobacteriota, and Actinobacteriota), indicating that soil fungi have a more sensitive relationship with forest succession compared with bacteria. The soil microbial community variation induced by forest succession was significantly affected by soil total phosphorus, dissolved organic carbon content and pH. Compared to deterministic processes, stochastic processes mainly dominated the community assembly of soil microbial communities. Meanwhile, the relative importance of stochasticity in soil fungal communities increased in the later stages. In Particular, dispersal limitation and drift accounted for a large proportion of bacterial and fungal community assembly, respectively. In addition, the co-occurrence networks of soil microbial communities became more complex as succession proceeds. Soil bacteria and fungi exhibited more competition and cooperation along the forest successional gradient. Collectively, our findings suggest that forest succession improves the complexity of soil microbial interactions and the ecological stochasticity of community assembly in Phoebe bournei-dominated forests, providing key insights into the relationship between microbial communities and forest succession.